Briefkaart. Betaald antwoord naar Curacao - (:unkn) unknown (My University, 2011)
This is a pre-paid reply postcard from Curacao with a 5 cent stamp.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Curacao; Postcards; Stamped envelopes--Curacao; Postal service--Registry system; 1893